Language abilities in children born to mothers diagnosed with diabetes: A systematic review and meta-analysis. (August 2021) - Arabiat, Diana; AL Jabery, Mohammad; Jenkins, Mark; Kemp, Vivien; Whitehead, Lisa; Adams, Gary
Abstract: Background: This meta-analysis reviewed and synthesized the available evidence on the association between intrauterine exposure to maternal diabetes and language abilities in children. Method: MEDLINE/PubMed, EMBASE, PsycINFO, Proquest Dissertations and Theses Global, and Google Scholar databases were searched through December 2020. Studies were systematically searched, and effect sizes were calculated using random effects models. Results: Twelve studies were identified for inclusion in this review, however, only 10 were included in the meta-analysis. Sample size ranged from 9 to 115 participants in the diabetes group and 28 to 8192 in the control and aged around 3 years. The pooled results of the meta-analysis showed a trend of decreased language abilities in receptive (z = −3.49, df = 10, I 2  = 34, p = 0.001), expressive language development (z = −2.29, df = 11, I 2  = 94%, p = 0.022) and general communication (z = −4.12, df = 4, I 2  = 2, p = 0.001) However, results showed a limited effect of maternal diabetes on children's language abilities after excluding high-risk categories such as children born to mothers with other gestational comorbidities, obesity and low socio-economic status. Conclusion: Our meta-analysis recognises that exposure to maternal diabetes during pregnancy intersects with other factors within the intrauterine environment to create the conditions for reduced language abilities in the child. Multiple factors may contribute to the observed differences between groups in the meta-analysis. A focus on interventions to maintain optimal blood glucose levels during pregnancy and to screen for early developmental delay after birth is recommended. Highlights: Maternal diabetes was significantly associated with reduced receptive and expressive language abilities in children. Speech communication was also reduced in children born to mothers with diabetes. Pre-existing diabetes was associated with decreased verbal intelligence. Obesity, gestational comorbidities and socioeconomics status are moderators of diabetes and language outcome.